Genetic and epigenetic factors of caries - Kostenko Євген Якович; Bilinskyi Олександр Ярославович (Actual Dentistry, 2021)
Summary. The paper analyzes the literature on the causes of caries, including the most common epigenetic factors, such as poor oral hygiene, adequate or deficient nutrition, the nature of food, biogeochemical and territorial factors, the content of microelements of water and soil, the level of environmental pollution, etc., as well as considering the genetic component, type of blood group, the structure of the hard tissues of the tooth, including a set of genes responsible for the occurrence and development of carious pathology. It was found that in conditions of fluoride and iodine deficiency, environmental factors have a critical role in the formation of the population-characteristic pattern of changes in dental status associated with the prevalence and intensity of caries. However, variations in these indicators may be partly mediated by the influence of genetically associated factors. The results of the analysis allowed to identify opportunities for the formulation of several independent analytical approaches that would help establish the significance of the genetic component in the structure of caries prognosis in terms of interaction with environmental conditions, actually determining how certain environmental factors can influence changes in genetic predisposition to caries. It can be summarized, that all currently available studies of the role of heredity in the risk structure of caries pathology is divided into two broad categories: identification of specific localized changes in genotype and verification of combinations or sets of such changes that can determine caries risk.